2022
DOI: 10.3390/vetsci9020070
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Radiographic Evaluation of Short- and Long-Term Outcomes of Different Treatments Adopted for Elbow Medial Compartment Disease in Dogs

Abstract: Medial compartment disease is a common occurrence in dogs affected by elbow dysplasia. Despite many treatments suggested in the literature, only few studies reported comparative outcomes in the short and long term. The aim of this study is to report and compare short- and long-term clinical and radiographic outcomes of dogs treated for medial compartment disease (MCD) by distal dynamic ulnar ostectomy (DUO), bi-oblique dynamic proximal ulnar osteotomy (BODPUO) and conservative management (CM). From 2016 to 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
1
2
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 42 publications
0
1
2
5
Order By: Relevance
“…Data regarding the long-term impact of ED/OA in dogs are sparse and have focused on the outcome of various treatment options and predominantly regarding MCPD. 17,18,39 In our study, there was no association found between ED grade and deterioration of the COI in the multivariable models. A high correlation was seen between lameness and all treatment variables as well as between previous surgery and rehabilitation treatment.…”
Section: Discussioncontrasting
confidence: 71%
See 1 more Smart Citation
“…Data regarding the long-term impact of ED/OA in dogs are sparse and have focused on the outcome of various treatment options and predominantly regarding MCPD. 17,18,39 In our study, there was no association found between ED grade and deterioration of the COI in the multivariable models. A high correlation was seen between lameness and all treatment variables as well as between previous surgery and rehabilitation treatment.…”
Section: Discussioncontrasting
confidence: 71%
“…A strength of this study is the availability of data for a large number of dogs with relatively high age that are not primarily seeking veterinary care. Data regarding the long‐term impact of ED/OA in dogs are sparse and have focused on the outcome of various treatment options and predominantly regarding MCPD 17,18,39 . In our study, there was no association found between ED grade and deterioration of the COI in the multivariable models.…”
Section: Discussioncontrasting
confidence: 60%
“…Essas alterações resultam em incongruência articular, instabilidade e desenvolvimento de osteoartrite. Anatomicamente, pode-se observar fragmentos ósseos soltos, irregularidades nas superfícies articulares e remodelação óssea (Schultz et al, 2008;Ribeiro, 2011;Coppieters et al, 2015;Eljack & Bottcher, 2015;Vezzoni & Benjamino, 2021;Pinto et al, 2021;Serrani et al, 2022).…”
Section: Introductionunclassified
“…Além do tratamento médico, o manejo das malformações ósseas frequentemente requer uma abordagem multidisciplinar, envolvendo ortopedistas, fisioterapeutas, nutricionistas e, em alguns casos, geneticistas. A reabilitação e o suporte contínuo são essenciais para maximizar a funcionalidade e a independência dos indivíduos afetados, bem como para prevenir complicações secundárias, como a artrite precoce ou a perda de mobilidade (Williauer & Vasseur, 1987;Zhu et al, 2012;Lavrijsen et al, 2014;Coppieters et al, 2015;Eljack & Bottcher, 2015;Konig & Liebich, 2021;Vezzoni & Benjamino, 2021;Pinto et al, 2021;Serrani et al, 2022;Ettinger et al, 2023). Baseado nisso, o objetivo deste trabalho é descrever o Research, Society and Development, v. 13, n. 6, e3813646028, 2024 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v13i6.46028 desenvolvimento anatômico dos membros, além de apresentar as alterações anatômicas e clínicas das principais malformações apendiculares em cães.…”
Section: Introductionunclassified
“…1-5 Also, assessing the severity of elbow OA over time facilitates evaluation of treatments aimed at slowing the progression of OA. 6,7 Elbow OA in dogs has traditionally been assessed by means of radiography, with several available grading schemes, including the International Elbow Working Group (IEWG) grading scheme, Results of using multiplanar reconstructed CT images for assessing elbow joint osteoarthritis in dogs are consistent with results of radiographic assessment…”
mentioning
confidence: 99%